SAT0133 Prevalence of type 2 diabetes and evaluation of patient characteristics among patients with and without ra from community rheumatologyclinics. (12th June 2018) - Alemao, E.; Ferri, L.; Paul, D.; Marshall, A.; McDonald, L.; Rao, A.; Anupindi, V. R.; Craig, G.; Knapp, K.
Abstract : Background: RA and type 2 diabetes (T2D) have common core pathophysiologic pathways, such as insulin resistance and increased glycated end products related to endothelial dysfunction, which may portendcardiovascular disease. 1 Currently there is limited real-world evidence of T2D prevalence among patients (pts) with RA. Objectives: To estimate the prevalence of T2D and insulin resistance among pts with RA vs control (osteoarthritis [OA] pts). To evaluate characteristics among RA pts with/without T2D. Methods: A retrospective study was conducted ona subset of the JointMan database (an electronic medical record of >6000 ptsfrom >10 providers. At each visit, diagnosis, medications, test results, co-morbidities and demographic data were collected. Pts aged ≥18 years with ≥2 diagnoses of RA or satisfying ACR criteria from 1 Jan 2009 to 30 Nov 2017 were included with a control group (pts with ≥2 OA diagnoses in the same period). Pts were considered to have T2D if they had a diagnosis code, diabetic medications prescription, HbA1c ≥6.5%, random glucose test ≥200 mg/dL or prior report ofT2D. Between-group prevalence was compared using a chi-squared test and characteristics of pts with/without T2D were compared using Fisher's exact, chi-squared and Mann-Whitney tests. Results: Data were analysed from 4181, 1157 and 1626 pts in RA-only, OA-only and dual (RA plus OA) cohorts, respectively. The RA-only cohort was younger and had a lower proportion of white pts compared with other cohorts (Table). T2D prevalence was significantly higher in the dual cohort (24.3%, n=395) vs RA-only (16.2%, n=676; p<0.001) and OA-only cohorts(10.5%, n=121; p<0.001). T2D prevalence was significantly higher in the RA-only vs OA-only cohorts (p<0.001). Sicca and Sjögren's syndromes were more prevalent co-morbidities in pts with RA only with vs without T2D (16.3 vs13.0%; p=0.023) and a similar trend was observed for thyroid disorder (6.4 vs 3.7%; p=0.001). Conclusions: A higher prevalence of T2D was observed in pts with RA compared with controls. In addition, co-morbidities of Sjögren's syndrome and thyroid disorder were higher in T2D pts with RA but not for dual RA plus OA. Reference: 1. de Groot L, et al. Arthritis Res Ther 2011;13:R205. Disclosure of Interest: E. AlemaoShareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, L.Ferri Employee of: Bristol-Myers Squibb, D. Paul Employee of: Bristol-Myers Squibb, A. Marshall Share holder of: Bristol-Myers Squibb, Employee of:Bristol-Myers Squibb, L. McDonald Employee of: Bristol-Myers Squibb, A. Rao Consultant for: Bristol-Myers Squibb, V. Anupindi Consultant for: Mu Sigma, G.Craig Share holder of: Discus Analytics, Grant/research support from: Bristol-Myers Squibb, Consultant for: Premera Blue Cross/Blue Shield of Washington and Alaska, Celgene, Bristol-Myers Squibb, Genentech, Novartis, Employee of: Arthritis Northwest, Paid instructor for: Washington State University Elson Floyd School of Medicine; University of Washington, Speakers bureau: Bristol-Myers Squibb, UCB, Genentech, Celgene, Novartis, Abbvie, Sanofi/Regeneron, Eli Lily, K. Knapp Shareholder of: Discus Analytics, LLC, Employee of: Discus Analytics, LLC